Changes in microstructure, quality and water distribution of porcine longissimus muscles subjected to ultrasound-assisted immersion freezing during frozen storage. (May 2019) - Zhang, Mingcheng; Xia, Xiufang; Liu, Qian; Chen, Qian; Kong, Baohua
Abstract: The effect of ultrasound-assisted immersion freezing at 180 W (UIF-180) on the microstructure, quality and water distribution of porcine longissimus muscles during frozen storage was evaluated. The size of the ice crystals increased with extended storage time, and UIF-180 samples had a smaller size and uniform distribution of ice crystals. The thawing and cooking losses in the UIF-180 sample were significantly lower than that in air freezing (AF) and immersion freezing (IF) samples ( P  < 0.05). AF samples had a higher cutting force at 0 days. During the 60–180 days of the storage period, the cutting force of UIF-180 samples was significantly higher than that of AF and IF samples ( P  < 0.05). Low field-nuclear magnetic resonance results showed that UIF-180 decreased water migration during frozen storage. UIF-180 samples had significantly lower lipid oxidation and higher redness than that of the AF and IF samples ( P  > 0.05). Overall, UIF at particular powers is an efficient method in reducing quality deterioration of muscles during long-term frozen storage. Highlights: UIF-180 sample had small and uniform distribution of ice crystals during storage. UIF treatment reduced the thawing and cooking losses and lipid oxidation of samples. UIF-180 samples had a shorter T 2 relaxation time during frozen storage. UIF at certain powers is as an efficient method in reducing quality deterioration.